2021
DOI: 10.1021/jacs.1c07978
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Glycolaldehyde Enol (HOHC═CHOH) in Interstellar Analogue Ices

Abstract: Glycolaldehyde is considered the entry point in the aqueous prebiotic formose (Butlerow) reaction although it mainly exists in its unreactive hydrated form in aqueous solution. The characterization of the more reactive nucleophilic enol form under interstellar conditions has remained elusive to date. Here we report on the identification of glycolaldehyde enol (1,2-ethenediol, HOHCCHOH) in low temperature methanol-bearing ices at temperatures as low as 5 K. Exploiting isotope labeling and isomer-selective phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 67 publications
4
39
0
Order By: Relevance
“…In agreement with the results of Kleimeier et al , 18 our computed equilibrium geometry of Z - 4 indicates a non-planar structure (the CC–O–H dihedral angle being about 25°), which should result in a moderate dipole moment component along the c -axis of the molecule ( μ c = 0.97 D). However, no μ c -allowed transitions could be observed in the spectrum.…”
supporting
confidence: 91%
“…In agreement with the results of Kleimeier et al , 18 our computed equilibrium geometry of Z - 4 indicates a non-planar structure (the CC–O–H dihedral angle being about 25°), which should result in a moderate dipole moment component along the c -axis of the molecule ( μ c = 0.97 D). However, no μ c -allowed transitions could be observed in the spectrum.…”
supporting
confidence: 91%
“…As extracted from astrophysical ice analog mixtures of carbon monoxide (CO)-methane (CH 4 ) and carbon monoxide (CO)-ethane (C 2 H 6 ), aldehydes can be formed via the exoergic radical-radical recombination of the formyl radical (HCO•) with any hydrocarbon radical (R•) ( 14) and (15) (Abplanalp et al 2016b;Bennett et al 2005aBennett et al , 2005bTurner et al 2021); formyl itself is formed through the addition of a suprathermal hydrogen atom to carbon monoxide (13), while hydrocarbon radicals are generated through interactions of GCR proxies with closed-shell hydrocarbons such as methane (1) and ethane (12). Aldehydes act as precursors to their enol tautomers, such as vinylalcohol-also known as hydroxyethylene-(C 2 H 3 OH) and cis/trans 1-methyl-2-hydroxyethylene ((CH 3 )HCCH(OH)), which was not identified in the present search (Abplanalp et al 2016b;Kleimeier et al 2021a;Kleimeier & Kaiser 2021b). Note that acetaldehyde (CH 3 CHO), along with vinylalcohol (C 2 H 3 OH) and propylene oxide (c-C 2 H 4 O), were also identified in the ethylene-carbon dioxide ice mixture exposed to ionizing radiation; in this system, the reaction was initiated by suprathermal hydrogen atoms and additions to the carbon-carbon double bond, followed by stabilization of the complex and/or isomerization prior to complex stabilization (Bennett et al 2005b;Bergantini et al 2018b)…”
Section: Formation Routes In Interstellar Icesmentioning
confidence: 87%
“…It remains to be seen if the versatile route of radical-radical reactions between formyl (HCO•) and an alkoxy (RO•) can be expanded to form ethylformic acid ester (HCOOC 2 H 5 ) via the reaction of formyl with ethoxy (C 2 H 5 O•) (26). It shall be highlighted that besides the recombination of the formyl radical (HCO•) with the methoxy radical (CH 3 O•) to form methylformic acid ester (HCOOCH 3 ), via reaction (25), a recombination with the hydroxymethyl radical (•CH 2 OH) leads to the astronomically observed glycolaldehyde (HCOCH 2 OH) (reaction (27);Maity et al 2015Maity et al , 2014bKleimeier et al 2021a;…”
mentioning
confidence: 99%
“…Its lowest energy conformer (trans), which is the one expected to be detected in interstellar conditions (the cis form is 2237 K higher in energy), has vanishing dipole moment because of symmetry, so it cannot be detected by rotational emission. The route (4) was favoured by the experimental work by Kleimeier et al (2021), in which HCOCHO was identified after electron irradiation of methanol-bearing interstellar ice analogues. However, we note that the experiments by Leroux et al (2020) showed that the hydrogenation of HCOCHO ices does not lead to the formation of more complex species (e.g.…”
Section: Hmentioning
confidence: 99%
“…Recently, the experiments on interstellar ice analogues carried out by Kleimeier et al (2021) have identified the enol form of glycolaldehyde, (Z)-1,2-ethenediol (CHOH) 2 , a species that might be a key precursor in the formation of sugars in both interstellar and prebiotic chemistry (e.g. Kitadai & Maruyama 2018).…”
Section: Introductionmentioning
confidence: 99%